Solve for x -3(-2x+3)-3x=3

Math
-3(-2x+3)-3x=3
Simplify -3(-2x+3)-3x.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-3(-2x)-3⋅3-3x=3
Multiply -2 by -3.
6x-3⋅3-3x=3
Multiply -3 by 3.
6x-9-3x=3
6x-9-3x=3
Subtract 3x from 6x.
3x-9=3
3x-9=3
Move all terms not containing x to the right side of the equation.
Tap for more steps…
Add 9 to both sides of the equation.
3x=3+9
Add 3 and 9.
3x=12
3x=12
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3x=12 by 3.
3×3=123
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3×3=123
Divide x by 1.
x=123
x=123
Divide 12 by 3.
x=4
x=4
Solve for x -3(-2x+3)-3x=3

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top